Mammary transcriptome analysis of lactating dairy cows following administration of bovine growth hormone. (25th May 2016) - McCoard, S. A.; Hayashi, A. A.; Sciascia, Q.; Rounce, J.; Sinclair, B.; McNabb, W. C.; Roy, N. C.
Abstract : The galactopoietic effect of growth hormone (GH) in lactating ruminants is well established; however the mechanisms that mediate these effects are not well understood. The first objective of this study was to determine the effect of GH on the synthesis of the major casein and whey proteins. The second objective was to identify the genes and pathways that may be involved in mediating the effect of GH on milk synthesis. A single subcutaneous injection of a commercially available slow release formulation of GH (Lactatropin ® ), or physiological saline solution (control) was administered to non-pregnant dairy cows ( n =4/group) in mid-late lactation. Milk samples were collected for composition analysis and mammary lobulo-alveolar tissue was collected postmortem 6 days post injection. Gene expression profiles were evaluated using either a 22 000 bovine complementary DNA microarray or quantitative PCR (qPCR), and microarrays were validated by qPCR. The yield of all the major casein and whey proteins was increased 32% to 41% in GH-treated cows, with the exception of α -lactalbumin yield which was elevated by 70% relative to controls. Treatment with GH treatment tended to increase the concentration of α -lactalbumin but had no effect on the concentration of any of the major milk proteins. Messenger RNA (mRNA) abundance of the major whey and casein genes, with the exception of α -s2-casein, was increased in response to GH compared with controls, which is consistent with the positive effect of GH on milk production. Treatment with GH treatment influenced the mRNA abundance of genes involved in cell growth and proliferation, transcriptional and translational regulation, actin cytoskeleton signalling, lipid metabolism and cell death. This study has provided new insights into the cell signalling that may be involved in mediating the effect of GH on milk production in the mammary gland of lactating dairy cows.